The Effect of Cosmocracy in the Metaverse World on National Security (Arkycia Metaverse Case Study) - Ken Bimo Sultoni; Jihan Marsya Azahra; Puspitasari (Budapest International Research and Critics University, 2022)
Mark Zuckerberg as the Facebook CEO who oversees the Instagram and Whatsapp platforms said that this was done as part of the company's rebranding. Metaverse is about bringing life back together, to recover all the hardships brought on in the original world. The anticipated truth and the future of the next evolution that is expected to develop by human hands. The technology used will involve the development of a combination of virtual reality and other technologies. The world of the Metaverse is very large, but in this case, the researcher will try to review further related to the scenario or influence that can be caused by the metaverse world, especially in relation to developing and implementing the concept of a utopian cosmocracy into something that might happen and have an impact on the reality that occurs in the world real.